Topical chemotherapy with mitomycin C in a feline corneal squamous cell carcinoma - Delgado, Esmeralda Costa (JFMS Open Rep, 2020)
CASE SUMMARY: A 9-year-old cat was presented with a right globe lesion of 6 months’ duration. A large pink elevated mass covering two-thirds of the right cornea was detected. The corneal mass was surgically removed by superficial keratectomy and diagnosed by histopathology as a squamous cell carcinoma (SCC). The surgical procedure led to a relatively transparent cornea, but recurrence was likely. To avoid relapse, 1 month after surgery three cycles of mitomycin C 0.04% eye drops were applied q8h for 15 days on/15 days off. No local or systemic side effects were seen, and no recurrence was detected after 1 year of follow-up. Topical mitomycin C was successfully used as adjuvant local chemotherapy agent and prevented relapses owing to its cytostatic effect. RELEVANCE AND NOVEL INFORMATION: SCCs are relatively common in feline patients, especially in the non-pigmented extremities of the nose, ears and eyelids, but with the cornea being a rare location. They rarely metastasise and they seldom relapse locally after surgical excision. Surgical-free margins of 2 cm are advisable to prevent relapses. Corneal tumours are rare, as the cornea is avascular; corneal transparency is essential to assure clear vision. In corneal SCC this margin is impossible to achieve without enucleation. In the present report, surgical removal of the neoplasm was combined with topical administration of the anticancer drug mitomycin C and a good prognosis was obtained. This combined treatment may be an appropriate therapeutic option for feline corneal SCC.